The Effect of Bamboo Tali Leaf Tea on Leptin Levels in Rats Metabolic Syndrome - Ani Rosa Putri Ayu Mujayanah; Yulia Sari; Shanti Listyawati (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Metabolic syndrome is a threat to health problems in the world, namely a group of metabolic disorders that occur simultaneously. Obesity is a risk factor for metabolic syndrome. Fat accumulation causes insulin resistance and leptin resistance resulting in weight gain. Tali bamboo leaf tea contains a natural source of antioxidants that can increase insulin sensitivity so that it can reduce leptin levels. This study aims to determine the effect of bamboo1tali leaf tea on leptin levels in rats with metabolic syndrome. This type of research is experimental laboratoric with a Pre-Post Test with a Control Group design. Wistar male white rats, 8 weeks old, and 150 – 250 grams in weight, were fed HFHF (High Fat High Fructose) for 14 days, induced by Nicotinamide and Streptozotocin. Then, the rats were divided into 5 groups, namely negative control, positive control, and 3 treatments of tali bamboo leaf tea (300, 600, and 900 mg/200 g BW) for 28 days. Measurement of leptin levels using the ELISA method.Bamboo leaf tea had a significant effect (p <0.005) on leptin levels in rats with metabolic syndrome. The largest decrease in leptin levels occurred in the TDB3 group which was 82.8% and the lowest decrease in leptin levels occurred in the TDB1 group which was 34.8%. Bamboo leaf tea doses of 300, 600, and 900 mg/200 g BW reduced leptin levels in rats with metabolic syndrome for 28 days.